Finite element analysis of reinforcement design of voided concrete deck slab - Lian Ni, Koong (2019)
Voided concrete deck slab is one of the options for concrete bridge deck design. The most common problem that a deck slab will usually face is that the numbers of reinforcement provided are not sufficient to sustain the load with the increased number of vehicles. Therefore, it is necessary to check whether the reinforcement is adequate to sustain the loads. Unfit or improper design can lead to the failure of a structure. A model of voided concrete deck slab was analysed by manual calculation and also designed in ANSYS software. There are several methods can be used to analyse the behaviour of voided concrete deck slab. However, among all these methods, finite element method and probabilistic method will be a very effective method to obtain the strength and behaviour of voided concrete deck slab. This analysis is to investigate the adequacy of reinforcement bar in a concrete bridge deck slab and also to determine the response behaviour of voided concrete deck slab. This research will mainly focus on the reinforcement and the probabilistic analysis of a voided concrete deck slab. The length of deck slab that will be tested is 20m. The values for the input variables are generated randomly by using Monte Carlo Simulation with given mean values and standard deviation or as prescribed samples using Response Surface Method. 10000 simulations had been made to make sure the analysis values obtained are more precise and uniform. Here, the study was conducted to prove that a voided concrete deck slab under the existence of randomness and uncertainty can be analyzed quickly and efficiently by applying probabilistic finite element analysis using ANSYS.